Evaluation of the Implementation of the Independent Curriculum Using the CIPP Model - armizal yanriko; Waskito Waskito; Arwizet Karudin; M Giatman (JETL (Journal of Education, Teaching and Learning), 2025)
The implementation of the Merdeka Curriculum in vocational schools requires systematic evaluation to ensure its effectiveness and relevance to industry needs. This study aimed to evaluate the implementation of the Merdeka Curriculum in the Welding Engineering Department of SMK Negeri 1 Bengkalis using the CIPP (Context, Input, Process, Product) evaluation model. A quantitative descriptive method was employed, involving teachers, students, and stakeholders as respondents. The context evaluation showed that curriculum goals were highly relevant and aligned with welding industry demands (85%, Very Good). Input evaluation indicated adequate teacher competence and learning materials, but limited infrastructure support (68%, Fair). The process evaluation revealed effective application of project-based learning, with high student engagement and active participation. Product evaluation showed that students achieved strong learning outcomes and welding competencies, and expressed general satisfaction with the curriculum. Overall, the results suggest that the Merdeka Curriculum is suitable for vocational education and supports student-centered learning. However, improvements in infrastructure and supervision are needed to strengthen the implementation. This study highlights the importance of ongoing curriculum evaluation to ensure alignment with industry expectations and the successful development of student competencies